Faktor Perubahan Alih Fungsi Lahan Pertanian Akibat Pembangunan Kawasan Aerotropolis Kulon Progo dan Dampaknya Terhadap Tata Guna Lahan LP2B, Pemukiman dan Pariwisata - Dea, Rosaria Gracia (Local Engineering, 2024)
The development of the Aerotropolis area in Kulon Progo Regency causes frequent changes in agricultural land use to residential areas, hotels, restaurants, and other infrastructure. The excessive rate of conversion of agricultural land will have a negative impact on Kulon Progo Regency. Therefore, it is necessary to know the factors causing changes in agricultural land use and their impact on LP2B areas, residences, and tourism. The research method used is descriptive-analytical with statistical data; observations of situational conditions and the results of interviews regarding the problem being studied will be analyzed and then explained more specifically and in depth. The results of the analysis show that the phenomenon of land conversion in Kulon Regency is influenced by internal factors, namely the strategic location of agricultural land and its proximity to public facilities. The productivity of the agricultural sector has decreased due to difficult farmer regeneration, which causes economic factors to emerge. Apart from that, it is also influenced by external factors, namely increasing population growth, increasing development of the trade and services sector, the COVID-19 pandemic, and government policies that facilitate the conversion of agricultural land. The impact is that land and agricultural productivity are decreasing while the area of residential areas and the tourism sector are increasing. As a result, the GDP growth rate in the agricultural sector decreased, while the accommodation and food and drink (tourism) sector and the service sector increased. This trend has the potential to reduce the implementation of LP2B in Kulon Progo Regency. Recommendations that need to be made are strengthening government policies regarding the protection of LP2B and the involvement of many parties from the community, private sector, NGOs (Non-Government Organizations), and local governments regarding the implementation of LP2B